1992
DOI: 10.1113/expphysiol.1992.sp003583
|View full text |Cite
|
Sign up to set email alerts
|

Indices for detection of changes in cardiorespiratory fitness during exercise training in man

Abstract: SUMMARYA decrease in the elevation of the linear relation of heart rate on oxygen consumption (HR/ V 0) throughout submaximal exercise testing has previously been used in individuals as an index of improvement in cardiorespiratory fitness after a moderate intensity training programme. In the present investigation, changes in HR/ VO elevation and its variability were quantified and compared with those of other similar indices. These comprised changes in the level of oxygen consumption or heart rate attained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This increase was evidenced by a decrease in cumulative heart rate and a 12 per cent improvement in their time to exhaustion on the treadmill, whereas the non-exercise group experienced a 5 per cent decrease in this measure following the 16 week program. This result is in accordance with previous studies (Norris et al 1990;Swaine et al 1992;Somers et al 1991) that reported a change in fitness following 10, 16 and 24 weeks of exercise, using a frequency and intensity similar to that of the current experiment.…”
Section: Discussionsupporting
confidence: 83%
“…This increase was evidenced by a decrease in cumulative heart rate and a 12 per cent improvement in their time to exhaustion on the treadmill, whereas the non-exercise group experienced a 5 per cent decrease in this measure following the 16 week program. This result is in accordance with previous studies (Norris et al 1990;Swaine et al 1992;Somers et al 1991) that reported a change in fitness following 10, 16 and 24 weeks of exercise, using a frequency and intensity similar to that of the current experiment.…”
Section: Discussionsupporting
confidence: 83%
“…unless otherwise indicated. The presence of a training effect was determined by analysing the heart rate-VI O # relationship [39,40]. A statistically significant decrease in the elevation of the computed regression line relating heart rate to VI O # after training was regarded as evidence of a training effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the ®rst test, subjects pedalled for 3 min at successive external power outputs (40, 60, 80, 100 and 120 W) at a constant 60 revolutions a minute. This protocol was terminated when the HR had risen to 140 beatsámin ±1 (an increase of 70 beatsá min ±1 over resting in a submaximal exercise intensity test allows adequate de®nition of the HR/ _ V O 2 relationship) (Swaine and Mary 1989). Steady-state _ V O 2 (values in millilitres per minute within 5%) and HR (values in beats per min within 5%) in the 3rd min of testing were used to calculate the HR/ _ V O 2 elevation.…”
Section: Exercise Testingmentioning
confidence: 99%
“…Alternatively, cardiorespiratory ®tness can be assessed from a submaximal test. A decrease in the elevation of the linear relationship between oxygen consumption ( _ V O 2 ) and heart rate (HR) is a reproducible and sensitive index for the quantitative detection of improvements in cardiorespiratory ®tness (Kappagoda et al 1979;Newell et al 1980;Swaine and Mary 1989); for a given _ V O 2 a lower HR can be achieved. In eect, this slope is the reciprocal of the oxygen pulse, i.e.…”
Section: Introductionmentioning
confidence: 99%